2019
DOI: 10.1007/s12565-019-00521-2
|View full text |Cite
|
Sign up to set email alerts
|

Various significant connections of the male pelvic floor muscles with special reference to the anal and urethral sphincter muscles

Abstract: The male pelvic floor is a complex structure formed by several muscles. The levator ani muscle and the perineal muscles are important components of the pelvic floor. The perineal muscles comprise the external anal sphincter, bulbospongiosus, superficial transverse perineal muscles, and ischiocavernosus. Although the connections of the muscles of the pelvic floor have been reported recently, the anatomical details of each muscle remain unclear. In this study, we examined the male pelvic floor to clarify the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…However, we have perceived them as a series of smooth muscle structures continuous with the longitudinal muscle of the rectum and have demonstrated their continuity and spatial distribution (Muro et al, 2018). Furthermore, we have reported that this series is surrounded laterally by continuous skeletal muscles (Suriyut et al, 2020). The levator ani is continuous with the external anal sphincter in the anterior and posterior regions of the anal canal, as illustrated in Figure 8.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…However, we have perceived them as a series of smooth muscle structures continuous with the longitudinal muscle of the rectum and have demonstrated their continuity and spatial distribution (Muro et al, 2018). Furthermore, we have reported that this series is surrounded laterally by continuous skeletal muscles (Suriyut et al, 2020). The levator ani is continuous with the external anal sphincter in the anterior and posterior regions of the anal canal, as illustrated in Figure 8.…”
Section: Discussionmentioning
confidence: 66%
“…Although the pelvic floor muscles have generally been considered independent, we previously reported that the muscle bundles of the skeletal muscles are connected to each other in the male pelvic floor (Suriyut et al, 2020). This finding suggests that skeletal muscles of the pelvic floor such as the levator ani and perineal muscles act as a complex rather than independently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has clarified that the external anal sphincter (EAS), superficial transverse perineal muscle (STP), and levator ani (LA) extend and surround the anterior and lateral sides of the urethra to form the EUS 12 . This means that the EUS is not an independent muscle, but a continuous structure with other pelvic floor muscles.…”
mentioning
confidence: 99%
“…We have reported the characteristic structure of the pelvic floor, in which the striated muscles share their muscle bundles and are continuous, and the smooth muscle occupies the space between them [11][12][13][14][15][16][17][18][19][20] . These studies suggest that striated and smooth muscles coordinate in anal function and pelvic floor support.…”
mentioning
confidence: 99%